Adult Learning and the Advantages of the Online Learning Experience - Stephanie Hoon; Penny Wilkins; Angela Perry (Westcliff University, 2018)
This paper discusses several benefits of the online educational experience, specifically as it pertains to the adult learner. The paper focuses on the aspects of collaboration, flexibility, and cultural opportunities. The work concludes that online education is ideal for adult learners because of the aspects of collaboration, flexibility, and diversity it provides utilizing the constructivist approach.